Long-term effects of dialectical behaviour therapy for posttraumatic stress disorder and cognitive processing therapy 9 months after treatment termination = Efectos a largo plazo de la terapia dialéctica conductual para el trastorno de estrés postraumático y la terapia de procesamiento cognitivo 9 meses después de la finalización del tratamiento - Vonderlin, Ruben; Priebe, Kathlen; Müller-Engelmann, Meike; Fydrich, Thomas; Steil, Regina; Resick, Patricia A.; Schmahl, Christian; Lindauer, Petra; Kleindienst, Nikolaus; Bohus, Martin (European journal of psychotraumatology, 2024)
Background: The complexity of posttraumatic stress disorder (PTSD) symptoms related to childhood abuse (CA) present challenges for effective psychotherapeutic treatment. Consequently, there is great interest in the long-term effectiveness of psychological treatments for this population. Objective: This study aims to investigate the long-term outcomes of Dialectical Behaviour Therapy for PTSD (DBT-PTSD) and Cognitive Processing Therapy (CPT) 9 months after treatment termination. Method: This is a long-term analysis from a randomised-controlled trial of DBT-PTSD versus CPT (registration number DRKS00005578). Initially, 193 individuals with CA-related PTSD were randomly allocated to receive either DBT-PTSD (n = 98) or CPT (n = 95). The primary outcome the Clinician-administered PTSD-Scale for DSM-5 (CAPS-5) was administred at baseline, treatment completion (15 months post-randomization) and at the 9-month follow-up. Secondary outcomes included self-reported PTSD severity (PCL-5), dissociation (DSS), severity of borderline symptoms (BSL-23), and psychosocial functioning (GAF). Results: No significant changes were observed in the primary (CAPS) and all other outcomes from post-intervention to 9-months follow-up in both the DBT-PTSD (CAPS: Mpost = 15.60, Mfollow-up = 14.93) and CPT group (CAPS: Mpost = 18.80, Mfollow-up = 17.41). Between-group analyses at 9-months follow-up were significantly in favour of DBT-PTSD compared to CPT with small to medium effect sizes on all outcomes ranging from d = 0.35 on the CAPS to d = 0.57 on the BSL-23 and GAF. Conclusions: Our results indicate that treatment effects of psychotherapy addressing complex presentations of PTSD persist 9 months after treatment termination. In addition, the superiority of DBT-PTSD as compared to CPT found at treatment termination, was confirmed at 9-months follow-up. Trial registration: German Clinical Trials Register identifier: DRKS00005578.. This study investigates the long-term effects of Dialectical Behaviour Therapy for Posttraumatic Stress Disorder (DBT-PTSD) and Cognitive Processing Therapy (CPT) on complex presentations of PTSD 9 months after treatment termination.In both treatment arms, treatment effects persisted over 9 months post-treatment termination across a wide range of outcomes.DBT-PTSD showed significant superiority over CPT at 9 months follow-up with differential effect sizes between d = 0.35 and d = 0.57. This study investigates the long-term effects of Dialectical Behaviour Therapy for Posttraumatic Stress Disorder (DBT-PTSD) and Cognitive Processing Therapy (CPT) on complex presentations of PTSD 9 months after treatment termination. In both treatment arms, treatment effects persisted over 9 months post-treatment termination across a wide range of outcomes. DBT-PTSD showed significant superiority over CPT at 9 months follow-up with differential effect sizes between d = 0.35 and d = 0.57.
Gesehen am 06.11.2024